Identity Regulation as Organizational Control: Producing the Appropriate Individual - Alvesson, Mats; Willmott, Hugh (Journal of Management Studies, 2002)
This paper takes the regulation of identity as a focus for examining organizational control. It considers how employees are enjoined to develop self‐images and work orientations that are deemed congruent with managerially defined objectives. This focus on identity extends and deepens themes developed within other analyses of normative control. Empirical materials are deployed to illustrate how managerial intervention operates, more or less intentionally and in/effectively, to influence employees’ self‐constructions in terms of coherence, distinctiveness and commitment. The processual nature of such control is emphasized, arguing that it exists in tension with other intra and extra‐organizational claims upon employees’ sense of identity in a way that can open a space for forms of micro‐emancipation.